Genetic and phenotypic variability and correlations between yield components of sunflower (Helianthus annuus) lines. - Ortegón, Alfredo (2016)
An experiment was conducted in August of 1991 under irrigated conditions at Rio Bravo, Tamaulipas, Mexico, in arder to observe the genetic and phenotypic variance, the direct and indirect correlation effects of six caracters on the grain yield of the 285, 386, 486, CM3 and VI sunflower lines, which are carriers of cytoplasmic mal e sterility. The results, of this group of lines, showed a high genetic variance in seed weight, plant height and reproductive periodo The characters of grain yield and oil content showed low genetic variance and low heritability, but a higher expected genetic adyance. The grain yield was high and positively correlated with the variables of head diameter, weight of 1000 seeds and vegetative period, but negatively to oil yield. The analysis of direct and indirect effects showed that the plant height, vegetative period and weight of 1000 seeds had a higher influence on the grain yield.